Etiology and treatment of amyotrophic lateral sclerosis - Rafael, Hernando (Am J Neurodegener Dis, 2017)
Background: To date all researchers conclude that the etiology of Amyotrophic lateral sclerosis (ALS) is not known. On the contrary, since August 2009, we believe that disease is of ischemic origin in the anterior surface of the medulla oblongata. Material and method: We present our surgical experience into 45 patients with ALS (bulbar form in 36 cases and spinal form in 9). Preoperative MRI scans revealed microinfarcts in the medulla oblongata and/or cervical cord. During surgery we found: 1) poor quality of omentum in most cases; 2) degenerative changes in the cervical spine; 3) anatomical anomalies at the V4 segments of the vertebral arteries; 4) moderate to severe atherosclerosis at both V4 segments; 5) unilateral absence or stenosis in the anterior-ventral spinal arteries (AVSAs). All patients received omentum on the anterior, lateral and posterior surface of the medulla oblongata, and in 9 cases, an additional segment at the C5-C6 level. Results: Neurological improvement was better during the first days or weeks after surgery than in the following months or years, in all patients. However, 13 patients suffered neurological impairment in about 4 months later, due to greater deterioration of the cervical spine, by contrast, 7 patients with mild ALS have experienced neurological improvement by 80 to 100% during a follow-up of 4 and 6 years. Conclusions: These results confirm that ALS is of ischemic origin in the intraparenchymal territory of the AVSAs and/or in anterior spinal artery caused by atherosclerosis and associated to anatomical variants in the V4 segments of the vertebral arteries. Because in contrast to this, its revascularization by means of omentum can cure (mild degree) or improve this disease.